1991
DOI: 10.1063/1.348884
|View full text |Cite
|
Sign up to set email alerts
|

Study of Si/GeSi p-n heterostructures

Abstract: The experimental results of a molecular-beam epitaxy grown Si/GeSi p-n heterojunction are reported. It is found that the current flow in these p-n heterojunctions shows a nonideality factor of about 1.5 at room temperature and 2.35 at liquid nitrogen temperature. The nonideal behavior of the Si/GeSi p-n heterojunction is attributed to the charges that are trapped at the heterointerface. Annealing the samples at temperatures higher than the growth temperature results in an increase in the density of defects as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…For an ideal p-n junction, the slope of C −2 versus V is a constant. Nevertheless, the defect states at the interface region also contribute to the capacitance at high voltage, and then lead to a change of the slope of C − 2 versus V [22,23]. As shown in Fig.…”
Section: Influence Of P-nc-si:h Buffer Layer On Cell Performancementioning
confidence: 93%
“…For an ideal p-n junction, the slope of C −2 versus V is a constant. Nevertheless, the defect states at the interface region also contribute to the capacitance at high voltage, and then lead to a change of the slope of C − 2 versus V [22,23]. As shown in Fig.…”
Section: Influence Of P-nc-si:h Buffer Layer On Cell Performancementioning
confidence: 93%
“…[107][108][109] For relaxed SiGe=Si HJs one can add the non-ideal current due to recombination in the depletion region and at the hetero-interface. [110][111][112][113][114][115][116] The C-V relationship of an abrupt n-Si=p-Ge HJ without interface states is given by 104,105,109…”
Section: Introductionmentioning
confidence: 99%
“…A major point of further study is the origin (and nature) of the observed extended defects. Of course, one should also consider possible contributions from interface states at the SiGe/Si interface (9,10). It should, finally, be remarked that the pronounced increase in J A for reduced etch depth is not related to a change in the depletion depth or the carrier doping density, as can be derived from the free carrier profiles in Fig.…”
Section: Reverse Current Densitymentioning
confidence: 95%